Novel aggregation-induced emission and thermally activated delayed fluorescence materials based on thianthrene-9, 9′, 10, 10′-tetraoxide derivatives. Issue 26 (24th February 2016) - Sun, Kaiyong; Jiang, Wei; Ban, Xinxin; Huang, Bin; Zhang, Zhaohang; Ye, Muyang; Sun, Yueming
Abstract : By introducing more proportion of carbazole, the newly designed molecule3tCzDSO2 integrates the features of AIE and TADF with extremely small Δ E ST . Abstract : Two novel luminescent molecules based on thianthrene-9, 9′, 10, 10′-tetraoxide derivatives, namedtCzDSO2 and3tCzDSO2, have been synthesized and characterized. The compoundtCzDSO2 emits intense aggregation-induced emission (AIE) with a high photoluminescence quantum yields ( Φ F ) of 0.92 at room temperature in the solid state. Simultaneously, by increasing the proportion of carbazole units, 3tCzDSO2 exhibits both AIE and thermally activated delayed fluorescence (TADF) in the solid state with Φ F of 0.19 in air and 0.41 in N2 atmosphere. The two compounds also display a bathochromic effect due to their intramolecular charge transfer (ICT) attribute. The time-dependent DFT predicted the singlet and triplet splitting (Δ E ST ) values oftCzDSO2 and3tCzDSO2 to be 0.29 eV and 0.06 eV, respectively. The Δ E ST of3tCzDSO2 is small enough to allow efficient reverse intersystem crossing (RISC), leading to the TADF property at room temperature. As a result, the molecular design provides a simple and effective approach to integrate the features of AIE and TADF into one compound.